DESCRIPTION OF KNOWLEDGE LEVEL, ATTITUDES, AND BEHAVIOR IN THE USE OF FACIAL WHITENING COSMETICS AMONG FEMALE STUDENTS OF THE FACULTY OF MEDICINE, HKBP NOMMENSEN UNIVERSITY MEDAN, 2024 - Purba, Cory Anita; Panjaitan, Rudyn Raymond; Sihombing, Jenny Ria (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
This is a descriptive study with a crossectional design. With the total sampling technique is obtained 71 female respondents who used whitening cosmetics. The results showed that the average age of the class of 2021 is 21.2 years, the average age of the class of 2024 is 20.2 years and the average age of the class of 2023 is 18.8 years. The description of the level of knowledge is sufficient (52.1%). The majority of the level of knowledge is found in the class of 2023 (59.1%). Description of the level of capable attitude (81.7%). The level of attitude that is able to be the majority in the class of 2022 (89.5%). The description of the level of behavior is quite capable (54.9%). The level of behavior is quite majority in the class of 2022 (79%).